(untitled) (REMUNOM, 2025)
This study, developed as a final project for the Tocantins State University (UNITINS), focuses on analyzing the risks associated with variable income investments in the Brazilian financial market. The work has the following specific objectives: to clearly and comprehensively present the risks inherent to this asset class; to identify and categorize the main types of risks involved; to verify the impact of the high volatility characteristic of the Brazilian stock market on investor returns; and to examine the influence of domestic macroeconomic and political factors on the performance and behavior of variable income assets. The methodology employed is qualitative in nature, based on bibliographic and documentary research, with an explanatory approach. Through a review of specialized literature, academic articles, financial institution reports, and market data, the study seeks to explain the cause-and-effect relationships behind the identified risks. The research deepens the conceptualization of fundamental risks, such as market risk—associated with losses arising from fluctuations in stock prices, interest rates, and exchange rates—and liquidity risk—related to the difficulty of converting an asset into currency without significant loss of value. Additionally, the work details the characteristics and risks inherent to the main variable income instruments available in Brazil, such as shares (common and preferred), BDRs (Brazilian Depositary Receipts), debentures, ETFs (Exchange Traded Funds) and Real Estate Investment Funds (FIIs). It is concluded that a detailed understanding of this type of risks and the instruments that incorporate them is a fundamental requirement for investors to be able to outline conscious strategies, manage their portfolios effectively and make more informed and safe investment decisions in the complex environment of the Brazilian capital market.